β phase transformation and dynamic recrystallization of a metastable β -Ti6554 alloy during electrically assisted tension - Wu Chuan; Liu Bao Xi (Journal of Materials Research and Technology)
Phase transformation of orthogonal cube α'' and close-packed ω and dynamic recrystallization of β (β-DRX) are observed in a metastable β titanium alloy during electrically-assisted tension (EAT). Their volume fractions, sizes, shapes, and spatial distribution directly determine the formability and mechanical properties. Elucidating the mechanisms of the phase transformation and β-DRX is a necessary step to understand the relationship between microstructure and properties during EAT. Uniaxial EAT tests were carried out on a metastable β alloy Ti–6Cr–5Mo–5V–4Al (Ti6554) at electric current ranging from 9 to 60 A. The true stress strain curves, work hardening and flow softening, stress-induced α'' and ω phase transformation, and β-dynamic recrystallization were analyzed via various characterization methods. Results demonstrated that the macroscopic stress-strain curves can be divided into four stages according to work hardening rate and index. X-ray diffraction (XRD) combined with electron backscatter diffraction (EBSD) indicates that the α'' phase can be transformed from the β matrix phase at ∼20 A lower current range, while begins to be decomposed with the increase of current. In addition, pole figures manifest that classical orientation relationship (OR) can be identified between the β and α'', while OR is gradually blurred with the disappearance of α'' variants until to 40 A. As the current exceeds over 50 A, homogeneous β-DRX occurs in the center of deformation zone. High-resolution scanning transmission electron microscopy (HRS-TEM) analysis discloses the β → ω→α''→β and α activation sequence in the Ti6554 alloy during EAT. To further explain the transformation, decomposition, and DRX mechanisms, the Cr, Mo, V, and Al element diffusion maps are analyzed via EDS (energy-dispersive X-ray spectroscopy). Matched hot tension was performed and compared with EAT to disclose the Joule heating and athermal effects on the microstructural evolution of Ti6554 alloy during EAT. This work can provide valuable guidance in tailoring microstructure and properties of metastable β-titanium alloys during electrically assisted processing.